Reduced Risk of Reoperations With Modern Deep Brain Stimulator Systems: Big Data Analysis From a United States Claims Database - Wu, Chengyuan; Nagel, Sean J.; Agarwal, Rahul; Pötter-Nerger, Monika; Hamel, Wolfgang; Sharan, Ashwini D.; Connolly, Allison T.; Cheeran, Binith; Larson, Paul S. (Frontiers in Neurology, 2021)
Objective There have been significant improvements in the design and manufacturing of deep brain stimulation (DBS) systems, but no study has considered the impact of modern systems on complications. We sought to compare the relative occurrence of reoperations after de novo implantation of modern and traditional DBS systems in patients with Parkinson’s Disease (PD) or Essential Tremor (ET) in the United States. Design Retrospective, contemporaneous cohort study Setting Multicenter data from the United States Centers for Medicare and Medicaid Services administrative claims database between 2016 and 2018. Participants This population-based sample consisted of 5,998 patients implanted with a DBS system, of which 3,869 patients had a de novo implant and primary diagnosis of Parkinson’s Disease or Essential Tremor. Follow-up of 3 months was available for 3,810 patients, 12 months for 3,561 patients, and 24 months for 1,812 patients. Intervention Implantation of a modern directional or traditional omnidirectional DBS system. Primary and Secondary Outcome Measures We hypothesized that modern directional systems would impact complication rates. Reoperation rate was the primary outcome. Associated diagnoses, patient characteristics, and implanting center details served as covariates. Kaplan-Meier analysis was performed to compare rates of event-free survival and regression models were used to determine covariate influences. Results Patients implanted with modern systems were 36% less likely to require reoperation – largely due to differences in acute reoperations and intracranial lead reoperations. Risk reduction persisted while accounting for practice differences and implanting center experience. Risk reduction was more pronounced in patients with PD. Conclusions In the first multicenter analysis of device-related complications including modern DBS systems, we found that modern systems are associated with lower reoperation rates. This risk profile should be carefully considered during device selection for patients undergoing DBS for PD or ET. Prospective studies are needed to further investigate underlying causes.